Current status of scientific data curation research and practices in mainland China - Ou, Shiyan (2021)
With the rapid growth in the body of scientific data, scientific research depends more and more on finding theories and knowledge from the data, and thus data-intensive scientific discovery has become the fourth paradigm of scientific research. Therefore, it is urgent to develop and adopt methods to support the collection, collation, preservation and utilization of scientific data. This paper provides an overview of scientific data curation research and practices in mainland China. Firstly, it reviews Chinese research articles on data curation and outlines the research status and progress in this area. Secondly, it surveys existing scientific data repositories or platforms in mainland China, and analyzes the gaps between China’s and other countries’ data curation practices.